Development and Validation of a Mobile Application for Early Childhood Nutrition Monitoring: A Multisensor-Based Non-Contact Anthropometric System - Yafie, Evania; Pramono; Sutama, I Wayan; Samawi, Ahmad; Khairuddin, Khairul Farhah Binti; Asyhari, Rahayu (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
Proper early childhood nutrition or a lack thereof is paramount in Indonesia because stunting—their most common outcome—can become both physically and mentally irreversible. Parents all too often find difficulty in the accurate and consistent monitoring of their children's nutritional status, which can prevent early identification of deficiencies. This study presents the Multisensor-Based Non-Contact Anthropometric System, a mobile application designed to monitor nutritional status of under-five children using multisensory images. The research had five phases, which are based on a modified ADDIE model (Analysis, Design, Development, Implementation and Evaluation). Parent questionnaires highlighted key nutritional concerns, as well barriers to growth due stunting during the Analysis phase. Design- to lay down the objectives and create educational content inside of the app. In Phase 3, Production; the app was developed and then reviewed by experts in content accuracy as well as media design and instructional strategies. During the implementation phase, in Malang City were given Pretest and Postest to 15 parents as a tester of this APP about testing practically and effectively. Results showed that there were significant improvements in parental knowledge and skills to monitor child nutrition status for stunting, with average expert validation scores of 92.6% (range:75 –100) on media design, 86.25% (67–97) on material content as well as instructional design 87.28%(70 -96). The MB-NCAS app is a valid, reliable and feasible dietary assessment instrument for nutritional monitoring among preschool children. Nonetheless, the lack of tech capabilities in some geographically and/or financially constrained regions is a barrier to wider utilisation. Future research should investigate the generalizability of this app in various settings and work toward increasing technological access to maximize migrant health.